Accelerator X-Ray Sources - Talman R. Richard (Berlin, Wiley-VCH Verlag GmbH &Co. KGaA, 2006)
This is the first monograph to cover in-depth the production of brilliant x-ray beams in accelerators, with emphasis on fourth generation designs, such as energy recovery linacs (ERL), fast cycling storage rings, and free electron lasers (FEL). Going beyond existing treatments of the influence of synchrotron radiation on accelerator operation, special emphasis is placed on the design of undulator-based beam lines, and the physics of undulator radiation. Starting from the unified treatment of electron and photon beams both as bunches of particles and as waves, the author proceeds to analyse the main components, from electron gun, through linac and arc lattice, to the x-ray beam line. Designs are given for both an ERL and a more conventional storage ring complex, and their anticipated properties are compared in detail. Space charge effects are analysed with emphasis on coherent sychrotron radiation and emittance dilution. Beam diagnostics using synchrotron radiation or laser wire (Compton scattering) are also analysed in detail. Written primarily for general, particle, and radiation physicists, the systematic treatment adopted by the work makes it equally suitable as an advanced textbook for young researchers.